2003
DOI: 10.1152/jn.00939.2002
|View full text |Cite
|
Sign up to set email alerts
|

Control Strategies Correcting Inaccurately Programmed Fingertip Forces: Model Predictions Derived From Human Behavior

Abstract: Fagergren, Anders, Ö rjan Ekeberg, and Hans Forssberg. Control strategies correcting inaccurately programmed fingertip forces: model predictions derived from human behavior. J Neurophysiol 89: 2904-2916, 2003. First published February 12, 2003 10.1152/jn.00939.2002. When picking up a familiar object between the index finger and the thumb, the motor commands are predetermined by the CNS to correspond to the frictional demand of the finger-object contact area. If the friction is less than expected, the object w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In a typical PG task, participants are required to use precision grip and lift an object to a designated height (Eliasson, Forssberg, Hung, & Gordon, 2006;Fagergren, Ekeberg, & Forssberg, 2003;Johansson, 1998;Johansson & Cole, 1994;Johansson, Riso, Hager, & Backstrom, 1992;Johansson & Westling, 1984, 1988a, 1988bUlloa, 2004). The two primary forces generated by the fingers are load force (which lifts the fingers) and grip force (which couples the fingers and the object).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In a typical PG task, participants are required to use precision grip and lift an object to a designated height (Eliasson, Forssberg, Hung, & Gordon, 2006;Fagergren, Ekeberg, & Forssberg, 2003;Johansson, 1998;Johansson & Cole, 1994;Johansson, Riso, Hager, & Backstrom, 1992;Johansson & Westling, 1984, 1988a, 1988bUlloa, 2004). The two primary forces generated by the fingers are load force (which lifts the fingers) and grip force (which couples the fingers and the object).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The information stored is used to set the parameters of the motor program that generates distributed muscle commands to the muscles producing the fingertip forces. The importance of such sensorimotor memory representations for the retrieval of parameters relevant to motor commands has been demonstrated regarding the prediction of object's weight Westling 1984, 1988;Westling and Johansson 1987), shape (Jenmalm and Johansson 1997;Jenmalm et al 2000), and frictional characteristics (Edin et al 1992;Fagergren et al 2003;Johansson and Westling 1984). At the same time, the motor system uses an efference copy of the motor command (Von Holst and Mittelstaedt 1950) produced when the movement is made to predict the sensory inputs of the motor act (Wolpert et al 1995) and compares it with the sensory input produced by the movement (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The function Slip Correction is used to stop the slip, and to adjust the force ratio based on the intensity of the slip: Fagergren et al [10] studied human behavior, and found that the best control strategy to stop slips was a burst increase of the grip force. Therefore, this same strategy is used in the above function to stop slips.…”
Section: ) Loading Phasementioning
confidence: 99%